Mediation in the Conflict of Legislation Resolution based on the Regulation of the Minister of Law and Human Rights Number 2 of 2019 - Syafrizal Syafrizal; Muhammad Kamil Akbar; Rahmad Ramadhan Hasibuan (Jurnal Hukum Novelty, 2019)
Introduction to The Problem: The authority possessed by the Ministry of Law and Human Rights after the enactment of Permenkumham No. 2 of 2019 this then raises problems both juridical and theoretical. Because it was explored further, no formula was found that regulates the authority of the Ministry of Law and Human Rights (in this case the Directorate General of Legislation) to harmonize legislation through mediation, both in Law No. 39 of 2008 concerning the State Ministry and Presidential Regulation No. 44 of 2015 concerning the Ministry of Law and Human Rights. In addition, the mediation mechanism used in resolving the harmonization of laws and regulations is a mistake, because it is not appropriate if the mediation mechanism is applied in the harmonization of laws and regulations that are public (public).Purpose/Objective Study: This paper objects are about the authority of the Minister of Law and Human Rights in the formation of Permenkumham No. 2 of 2019 and whether the Ministry of Law and Human Rights has the authority to mediate the disharmony of laws and regulations; then the next discussion about the mechanism and legal impact arising from the mediation.Design/Methodology/Approach: This paper used qualitative research method with juridical-normative as an analysis approach.Findings: the statutory regulations which are used as a basis to remember in Permenkumham No. 2 of 2019 no explicit delegation was found which ordered the formation of Permenkumham No. 2 of 2019, including the formulation which regulates the authority of the Directorate General of Legislation in completing the disharmony of legislation through mediation. Then in the case of mediation mechanism is a mechanism that is usually applied in cases that are private, where the parties act for and on their own behalf. so it becomes strange if mediation is used in resolving conflicting norms of laws and regulations which norms generally regulate, moreover the results of the mediation do not have binding legal force and do not provide legal impact on the validity of the norms of the agreed laws and regulations.Paper Type: Research Article